The Polemics of the Quest for Liberty in the Poetry of George Gordon, Lord Byron - Veyu, Ernest L.; Lum, Mary-Louisa (Mediterranean Journal of Social Sciences, 2011)
The quest for liberty in Lord Byron’s poetry is a polemical issue because most critics have termed it nihilistic and satanicsimply because the poet and his protagonists question Christian revelation and man-made laws. This article sets out to show that althoughLord Byron and the Byronic hero as can be seen in the different poems do question Christian revelation and flout a number of generallyaccepted moral values, they do so in an attempt to find answers, which might help the individual to understand the universe, and be ofhelp to the rest of mankind. The desire for liberty becomes the basic inspirational force, where conflict and warfare are justifiable pathwaysto the desired end. This paper also looks at the quest for liberty in Byron’s poetry from the perspective of the heroes’ ideals, justified byhuman nature and references to mythical rebels. Contrary to the generally accepted critical opinion that Lord Byron’s quest for liberty isessentially egocentric, this article seeks to show that the quest for liberty is the Byronic creed and the only constant element in the poet’sambiguous life alongside the detestation of cant. The article argues that the Byronic hero’s deconstruction of philosophical and sociopoliticalideals does not result from the poetic persona’s lawlessness as generally assumed, but from an innate justifiable call for change,first for the individual and then for the common good. Related to his search for liberty, there are a lot of polemical issues around Byron’snotion of the ideal, which are partly addressed in this paper.